French Fries-Like Bismuth Oxide: Physicochemical Properties, Electrical Conductivity and Photocatalytic Activity - Yayuk Astuti; Fauzan Musthafa; Arnelli Arnelli; Iis Nurhasanah (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Bismuth oxide synthesis using hydrothermal method has been conducted. This study aims to examine the effect of the hydrothermal reaction time on product characteristics and photocatalytic activity in degrading methyl orange dye. Bismuth oxide synthesis was initiated by dissolving bismuth nitrate pentahydrate (Bi(NO3)3.5H2O) and Na2SO4 in a distilled water and added NaOH gradually. The solution formed was transferred into a Teflon-lined autoclave and heated at 120 °C with time variations of 8–16 h. The formation of bismuth oxide was indicated by the vibrations of the Bi−O−Bi and Bi−O groups and the crystal structure consisting of a-Bi2O3, β-Bi2O3, and g-Bi2O3. In addition, the highest photocatalytic activity can be examined through several factors, such as: content of Bi−O−Bi and Bi−OH groups, crystal structure, band gap values, morphology, and surface area, acquired as a result of the effect of hydrothermal reaction time. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).